Object-oriented software system that performs FPM simulation in the area with moving boundary, and its application to the blood flow problem - Paszyński, Maciej (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents the project of object-oriented software system for modeling flows of fluids inside the area with moving boundary. The flow of a fluid is modeled by using Fluid Particle Model. Finite Elements mesh is generated on the boundary of the area, to allow calculations of stresses on the boundary, arisen from interaction of the fluid with the boundary. Here was presented the application of the system, that simulates the phenomenon of energy and mass transport in large arteries in man. The validity of the computational method was established by comparing the numerical results to medical measurements data. The architecture and results of Fluid Particle Model were presented to compare with the architecture and results of Finite Element models for blood flow in arteries, described in other publications.